Trade, tasks, and training: The effect of offshoring on individual skill upgrading - Jan Hogrefe; Jens Wrona (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
We offer a theoretical explanation and empirical evidence for a positive link between increased offshoring and individual skill upgrading. Skill upgrading takes the form of on-the-job training, complementing the existing literature, which mainly focuses on the retraining of workers after a direct job displacement through offshoring. To establish a link between offshoring and on-the-job training, we introduce an individual skill upgrading margin into the small-open-economy version of the Grossman and Rossi-Hansberg (2008) model of offshoring. In our model offshoring, by scaling up workers' wages, creates previously unexploited skill upgrading possibilities and, thus, leads to more on-the-job training. Using data from German manufacturing, we find strong empirical support for the prediction that increased offshoring is positively related to individual on-the-job training participation.
urn:nbn:de:bsz:21-opus-71152
Keywords: F10; F16; F61; 330; Offshoring; Tasks; Skill upgrading; On-the-job training